2022
DOI: 10.1109/access.2022.3146792
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Chaotic Permutation-Substitution Image Encryption Scheme Based on Logistic Map and Random Substitution

Abstract: Privacy is a serious concern related to sharing videos or images among people over the Internet. As a method to preserve images' privacy, chaos-based image encryption algorithms have been used widely to fulfil such a requirement. However, these algorithms suffer from a low key-space, significant computational overhead, and a lag in resistance against differential attacks. This paper presents a novel chaotic-based image encryption method based on permutation and substitution using a single Substitution Box (S-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…Then, the initial key is set to K ={x 0 , y 0 , a 0 , b 0 }, and the set initial key is updated by using Eq (9).…”
Section: A Key Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the initial key is set to K ={x 0 , y 0 , a 0 , b 0 }, and the set initial key is updated by using Eq (9).…”
Section: A Key Generationmentioning
confidence: 99%
“…When they are applied to image encryption, it takes a lot of time resulting in low encryption efficiency [4]. Therefore, researchers have proposed many different image encryption techniques, which contain image filtering [3], DNA coding [5], frequency domain transform [6], elliptic curves [7], compressive sensing [8], S-Box [9], fractional Fourier transform [10], neural networks [11], chaotic systems [12]- [14], etc. However, among these technologies, because of the special nature of chaotic systems, cryptography based on chaotic systems has become one of the most popular cryptographic schemes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [28] proposed a novel encryption scheme based on plaintext-dependent permutation and DNA encoding. Arif et al [29] suggested a novel encryption structure based on permutation and substitution using the Logistic map and random replacement. Pixels are scrambled using chaotic techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the prior works on image encryption [ 5 , 6 , 7 , 8 ] do not consider encryption speed in their design. In this work, we propose a lightweight image encryption algorithm considering the encryption speed.…”
Section: Introductionmentioning
confidence: 99%